2002
DOI: 10.1364/ol.27.001451
|View full text |Cite
|
Sign up to set email alerts
|

Colored conical emission by means of second-harmonic generation

Abstract: We predict that the combination of space and time modulational instabilities that occur by means of parametric wave mixing in quadratic media leads to colored conical emission. This phenomenon should be observed under conditions usually employed in second-harmonic experiments. (C) 2002 Optical Society of America

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…Again, since no theory has yet been developed for the MI of a bulk solitary beam, we must rely on the study of the MI of the FH+SH planeand-monochromatic eigenmode for disclosing the mechanism of the ST interplay. Indeed, in this case too the MI has been shown to lead to the spontaneous formation of angular dispersion, its gain curve having an X-type profile in the ST frequency domain [15].…”
mentioning
confidence: 91%
“…Again, since no theory has yet been developed for the MI of a bulk solitary beam, we must rely on the study of the MI of the FH+SH planeand-monochromatic eigenmode for disclosing the mechanism of the ST interplay. Indeed, in this case too the MI has been shown to lead to the spontaneous formation of angular dispersion, its gain curve having an X-type profile in the ST frequency domain [15].…”
mentioning
confidence: 91%
“…The nonlinear X waves are weakly localized nondiffracting and nondispersing wave packets characterized by a nonseparable spatiotemporal profile (propagation invariant solutions) [31,32], accessible in the normal group-velocity dispersion regime, the formation of which is triggered by conical emission [33]. In [34], it was theoretically demonstrated that an X wave at SH can be generated spontaneously by doubling a broad FH pump beam in the undepleted stage of its propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned experimental and theoretical results have stimulated further investigations on the role of Xwaves in nonlinear processes, as well as their description in terms of linear waves with a convenient envelope approach, [12,13,14,15,16,17,18,19,20,21,22,23] and their extension to quantized fields. [24] Within the active field of optical self-invariant pulsed beams (see among others [25,26,27,28,29,30,31]), it was recognized that X-waves may play a fundamental role in all the nonlinear processes encompassing spatio-temporal mechanics, well beyond the realm of quadratic frequency mixing where they had been originally observed.…”
Section: Introductionmentioning
confidence: 99%